Draining Development? Controlling Flows of Illicit Funds from Developing Countries - Reuter, Peter (World Bank, 2012)
The book provides the first collection of analytic contributions, as opposed to advocacy essays and black box estimates, on illicit financial flows (IFFs). Some of the chapter presents new empirical findings; others, new conceptual insights. All of them enrich the understanding of the dynamics of the illicit flows phenomenon. The book does not offer a new estimate of the global total of these flows because the phenomenon is too poorly understood. The chapters are based on papers first presented at a September 2009 conference at the World Bank. Each paper had one or two assigned discussants, and the revisions reflect the often searching critiques of the discussants, as well as additional comments from the editor and from two external peer reviewers. The chapters have been written to be accessible to non-experts. Following this introduction, the book has five parts: the political economy of illicit flows; illegal markets; to what extent do corporations facilitate illicit flows? Policy interventions; and conclusions and the path forward.